Analisis Konsumsi Rumah Tangga Kelompok Pendapatan Menengah-Bawah terhadap Kenaikan Tarif PPN di Jakarta - Aulia Saputra, Renata; Renata Aulia Saputra; Ranita Andini; Gina Arifah Seftiani; Jamila (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to analyze the impact of the Value Added Tax (VAT) rate increase to 12% in 2025 on the consumption patterns of lower-middle-income households in Jakarta. The research employs a descriptive quantitative approach using primary data collected through questionnaires distributed to 150 household respondents. The research instruments were tested using validity, reliability, and cross-tabulation (crosstab) analysis with the assistance of SPSS software. The results indicate that the VAT increase significantly affects purchasing power and alters household consumption behavior, with most respondents reducing non-essential consumption and shifting to cheaper substitute products. Furthermore, respondents perceive that the policy increases household economic burdens, although some still believe that the additional state revenue will be utilized for public infrastructure and welfare improvement. Overall, the VAT rate increase policy should be accompanied by social compensation programs to prevent further economic inequality among lower-middle-income groups